1988
DOI: 10.1021/jf00084a045
|View full text |Cite
|
Sign up to set email alerts
|

Total residues of 2-naphthoxyacetic acid, 2-(6-hydroxynaphthoxy)acetic acid, and 2-(7-hydroxynaphthoxy)acetic acid in tomato plants and fruit by high-performance liquid chromatography

Abstract: A study was undertaken to determine the total residues including the sugar-and protein-bound residues of 2-naphthoxyacetic acid (BNOA), 2-(6-hydroxynaphthoxy)acetic acid (6-OH-BNOA), and 2-(7hydroxynaphthoxy)acetic acid (7-OH-BNOA) in tomato fruit, blossoms, and leaves from plants treated with BNOA. Analyses were by high-performance liquid chromatography. There were no detectable residues of 7-OH-BNOA at a method sensitivity of 0.05 ppm on any of the samples and <0.05 ppm of BNOA and 6-OH-BNOA on the tomato fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Afterwards direct phosphorescence was also employed not only for the acid and the amide but also for ␤-NOA [10][11][12][13]. Once the chromatographic techniques became more significant in method development, reversed-phase liquid chromatography using C18 columns was employed for the analysis of these compounds using UV or fluorescence spectroscopy as detection techniques [14][15][16][17]. As regards liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) only few methods have been proposed for the determination of naphthalene polar derived compounds [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards direct phosphorescence was also employed not only for the acid and the amide but also for ␤-NOA [10][11][12][13]. Once the chromatographic techniques became more significant in method development, reversed-phase liquid chromatography using C18 columns was employed for the analysis of these compounds using UV or fluorescence spectroscopy as detection techniques [14][15][16][17]. As regards liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) only few methods have been proposed for the determination of naphthalene polar derived compounds [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 2-naphthylacetic acid (␤-NAA) has been determined in groundwater after an industrial leakage episode [18] and the presence of naphthylacetamide (NAD) has been studied in fruits and vegetables [20,22]. Regarding to the sample treatment, classical solvent extraction methods are currently used when analyzing fruits and vegetables [9,10,14,15], nevertheless QuEcHERS-based extraction procedures have been applied in the last few years to obtain cleaner extracts and higher preconcentration factors [18,20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a strong public pressure against the abolishment of their use in agricultural practices due to lack of regularly updated residue data. Synthetic auxins do not persist in plants, and their residues are expected to decrease below detection limits during growing (Archer and Stokes 1988;Bristol et al 1981). However, our previous results have shown that 4-CPA residues in some greenhouse tomatoes exceeded critical residue level of 0.5 mg kg-' (Gokmen and Acar 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organisation (WHO) regards 4-CPA and BNOA as slightly, and 2,4-D as moderately hazardous agrochemicals according to their acute toxicity, but there is no recommendation for the maximum permitted concentration (MPC) of 4-CPA and BNOA in foods (Tomlin 1994). Synthetic auxins do not persist in plants, and their residues decrease below detection limits as growth occurs (Archer and Stokes 1988;Bristol et al 1981), and therefore, this practice is safe from the viewpoint of consumers' health. However, repeated auxin treatment of flower clusters as they open also affects the mature fruits which are already present on the plant, resulting as higher auxin residue in the crop following initial harvesting.…”
Section: Introductionmentioning
confidence: 99%